Lumbar subdural haematoma after temporomesial resection in epilepsy patients-report of two cases and review of the literature - Mursch, Kay; Halatsch, Marc-Eric; Steinhoff, Bernhard J.; Behnke-Mursch, Julianne (Clinical neurology and neurosurgery, 2007)
We present two cases of lumbar subdural haematoma, both occurring after an uneventful temporomesial focus resection in patients suffering from medically intractable epilepsy. Initial symptom was back pain and sciatica 4 days and 13 days postoperatively, but no neurological deficits were observed. The diagnosis was confirmed by MRI. No risk factor could be identified. The pain responded well to conservative treatment and the haematomas resolved without neurological sequelae. A review of the literature reveals that the characteristics of spinal subdural haematoma following craniotomy are very similar. Six out of 12 reported cases occurred in temporal epilepsy surgery. All had a benign course and did not require an operative procedure. Back pain after epilepsy surgery may be caused by an intraspinal haematoma and should be investigated by MRI.